CCAFS field visit to Cauca, Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In November 2015, the Latin America and Carribean team and the Gender and Social Inclusion team of CCAFS went to the different communities in the Popayan area of Cauca which make up the Climate Smart Village (CSV) or TeSAC in Spanish. This visit was done in collaboration with the local partner: Ecohabitats. Photocredits: Manon Koningstein (CIAT)